The Role of Power Relations and Identification in Collaborative Knowledge Construction at Single Gender Online Forum - Aljared, Alyaa; Oztok, Murat (Proceedings of the International Conference on Networked Learning, 2024)
This short paper describes a research project that aims at exploring how identification and power relations contribute to learners’ knowledge construction in single gender online forum. This multiple case studies take place at five online classes in two female universities in Saudi Arabia. Data is collected from semi-structured interviews and group discussions. Qualitative content analysis of online discussions is used to investigate the extent in which collaborative knowledge construction was achieved by participants utilizing Gunawardena et, al. 1997 tool. In addition, Foucault discourse analysis is used to explore learners’ power relations and identification. The initial findings of the pilot study suggest that learners have imposed several power relations strategies in the discussion’s forum such as maintaining norms of online discussions; (2) maintaining norms of a good classmate; (3) criticizing, comparing and assessing each other's posts; (4) displaying personal information; (5) checkingothers' intellectual activities and messages; (6) comparing between oneself and others' actions and ways of thinking; (7) categorizing oneself and others ; and (8) excluding and including others. These behaviors were organized under three themes: normalisation, surveillance, and classification. Initial findings also showed that participants revealed parts of their identities while interacting with each other. The research will continue to investigate how these practices are influenced by the social and cultural settings and how this contributes to the quality of knowledge construction in online discussion forum.